Effectiveness of small-angle episiotomy on incisional laceration rate, suturing time, and incisional bleeding in primigravida: A meta-analysis - Zhang, Yan; Zhang, Jiaoyan; Zhao, Liang; Xiao, Lin; Tian, Jinhui; Fan, Wei (Frontiers in Medicine, 2023)
Objective To investigate the effect of small-angle lateral perineal incision on postoperative perineal rehabilitation in primiparous women. Method The Cochrane Library, PubMed, Embase, CINAHL, CNKI, WanFang, VIP, and the Chinese Biomedical Literature Database were searched for randomized controlled trials (RCTs) on the effect of small-angle episiotomy on postoperative maternal perineal wound rehabilitation in puerpera until April 3, 2022. Two researchers independently performed literature screening, data extraction and evaluation of risk of bias in the included literature, and statistical analysis of the data was performed using RevMan 5.4 and Stata 12.0 software. Result A total of 25 RCTs were included, with a total sample of 6,366 cases. Meta-analysis results showed that the use of small-angle episiotomy reduced incisional tearing [OR = 0.32, 95% CI (0.26, 0.39)], shortened incisional suture time [MD = −4.58 min, 95% CI (−6.02, −3.14)] and reduced incisional bleeding [MD = −19.08 mL, 95% CI (−19.53, −18.63)], with statistically significant differences (all p < 0.05). There was no significant difference in the rate of severe laceration between the two groups [OR = 2.32, 95% CI (0.70, 7.70), p > 0.05]. Conclusion The use of a small-angle episiotomy during vaginal delivery can reduce the incision tear rate without increasing the incidence of severe perineal laceration, while shortening the incisional suturing time and reducing incisional bleeding. It can be used clinically according to birth canal conditions of the maternal, the intrauterine condition of the fetus and maternal needs. Systematic Review Registration PROSPERO International Prospective Register of Systematic Reviews [CRD42022369698]; [https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=369698].